PENGUKURAN TINGKAT KEPENTINGAN DAN PELAKSANAAN SARANA WISATA BAGI WISATAWAN MELALUI METODE IMPORTANCE PERFORMANCE ANALYSIS (IPA) DI PUSAT KONSERVASI PANTAI PENYU PARIAMAN - Afrinaldi M (JURNAL PENDIDIKAN DAN KELUARGA, 2019)
The purpose of research is to determine the level of importance and the implementation of tourist facilities for tourists through the method of Importance Performance Analysis (IPA) in Pusat Konservasi Pantai Penyu in Pariaman city. This research consists of 3 indicators of tourism facilities, namely: basic tourism facilities, complementary tourism facilities, tourism support facilities. The type of this research is quantitative descriptive research with survey method. The population in this study are all tourists who visit Pusat Konservasi Pantai Penyu with large population and the number is not known for sure. Sampling technique is non probability sampling, by using purposive sampling. The number of samples in this study amounted to 81 tourists. Data collection using questionnaires based on Likert Scale that has been tested for its validity and reliability. Based on the research result, it is concluded that in general the level of importance and the implementation of tourism facilities for tourists through the method of Importance Performance Analysis of 40% of tourists stated that tourism is important and needs to be provided and maintained in the restaurants, daily market, souvenir shop and mushalla.